Pengaruh Arus Kas Dari Aktivitas Operasi, Aktivitas Investasi, Dan Aktivitas Pendanaan Terhadap Tingkat Likuiditas (Studi Pada Perusahan Sub Sektor Makanan dan Minuman yang Terdaftar di BEI) - Purnamaratri, Atika (Jurnal Ilmiah Mahasiswa FEB, 2016)
Liquidity and cash flow are very important issues in regarding the growth and survival sustainability of business and as well as the ability to handle manage and make a decision the trade-off between the concerning two source related parties of concern for financial managers. The This research aims at examining to reveal the effect of the three cash flow’s activities of cash flow on the liquidity level of liquidity of food and beverages companies. The data are collected through secondary source, i.e. the financial statement containing balance sheets and cash flow report of the food and beverages companies listed in Indonesia Stock Exchange during the year of 2010-2014 years. There are 16 companies are chosen as the research samples.The independent variable is the value of cash flow from operating, investinginvestment, and financing activities; ,mean while, the dependent one is the liquidity level as measured by cash ratio. The collected data are evaluated using classical assumption test before the hypothesis is assessed through multiple linear regression ,and t-test. The result of t-test reveals that the three activities of cash flow have significant effect on liquidity. with The significance levels of the operating cash flow, investment cash flow, and financing cash flow are amounted 0.,000, investment cash flow 0.,001, and financing cash flow 0.,040 respectively.Keywords: Operating cash flow; Investing cash flow; Financing cash flow; Liquidity Level; Food and beverages company.